2012
DOI: 10.1016/j.eswa.2012.02.053
|View full text |Cite
|
Sign up to set email alerts
|

SMS spam filtering: Methods and data

Abstract: Mobile or SMS spam is a real and growing problem primarily due to the availability of very cheap bulk pre-pay SMS packages and the fact that SMS engenders higher response rates as it is a trusted and personal service. SMS spam filtering is a relatively new task which inherits many issues and solutions from email spam filtering. However it poses its own specific challenges. This paper motivates work on filtering SMS spam and reviews recent developments in SMS spam filtering. The paper also discusses the issues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
84
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(87 citation statements)
references
References 32 publications
0
84
0
3
Order By: Relevance
“…This is by no means a unique problem for spam filtering, however, the limited available text per SMS makes the feature space sparse. This means that the samples, from the input space, are fewer and further apart, thus significantly reducing the data that the classifier has to work with [5]. Hidalgo et al [6] suggested the use of different features including: normalised words, character bi-and tri-grams and word bi-grams.…”
Section: Sms Spam Filteringmentioning
confidence: 99%
See 3 more Smart Citations
“…This is by no means a unique problem for spam filtering, however, the limited available text per SMS makes the feature space sparse. This means that the samples, from the input space, are fewer and further apart, thus significantly reducing the data that the classifier has to work with [5]. Hidalgo et al [6] suggested the use of different features including: normalised words, character bi-and tri-grams and word bi-grams.…”
Section: Sms Spam Filteringmentioning
confidence: 99%
“…However, they argue that the greatest disadvantage of this approach was that the features are fixed and can not be updated as the data changes and the nature of spam threat changes. The extracted features tend to be high dimensional requiring some sort of feature selection, or dimensionality reduction techniques [5,15,6].…”
Section: Sms Spam Filteringmentioning
confidence: 99%
See 2 more Smart Citations
“…Spam messages may fill user's mailbox engulfing important personal mails, wasting network bandwidth, consuming user's time and energy to sort through it [4]. Similarly, SMS spam messages are also nuisance to mobile subscribers as many mobile subscribers have suffered financial losses resulting from responding to SMS spam senders on premium rate numbers and signing up to expensive subscription services [5], [6].…”
Section: Introductionmentioning
confidence: 99%